Історичний досвід військового будівництва періоду Директорії в наукових і мемуарно-аналітичних працях військових істориків 20–30-х рр. ХХ ст. - Мельник, Р. П. (Видавництво Львівської політехніки, 2014)
Розглядається проблема, пов’язана з аналізом військового будівництва доби Директорії в українській мілітарній літературі 20–30-х рр. ХХ ст. Показано основні концептуальні підходи військових дослідників до вивчення історичного досвіду національного будівництва Збройних сил періоду існування Української Народної Республіки періоду Директорії. The thesis is devoted to complex research of Ukrainian military theoretical thought of the interwar period. Based on the deep analysis and systematization of a wade range of sources, it highlights the main stages of the conceptual approaches as to the principles of military engineering in the period of liberation competitions of 1917–1921 in the studies of military historians. It elucidates the role the Ukrainian military authors played in the exploration of the theoretical regulations of the military doctrine in the scientific papers as regards the national construction of the armed forces. The research examines the organization, areas and achievements of the scientific-historical and military-theoretical work of the military researchers of the diaspora. The author analyses historical experience of military engineering in the days of the national revolution 1917–1921 in scientific and memoirs-analytical works of military historians in the period of the Central Rada, Hetmanate, Directory and Western Ukrainian People’s Republic. It is emphasized that the dominant issue of the studies being analyzed and of the memoirs-analytical works of military historians was the history of the Ukrainian Revolution 1917–1921 and the analysis of the military engineering of that time. Deep comprehension and examination of the armed forces formation in the time of the liberation competitions allowed the military experts to start scientific theoretical work aimed at studying the military doctrine and therewith lay the foundation for building a regular military force with all its components.
Keywords: військове будівництво; Директорія; мілітарна література; construction of the armed forces; Directory; military historians